2020
DOI: 10.1002/chem.201905732
|View full text |Cite
|
Sign up to set email alerts
|

Tetrathiafulvalene‐Fused Heterabuckybowl: Protonation‐Induced Electron Transfer and Self‐Sensitized Photooxidation

Abstract: The electron donor tetrathiafulvalene (D 1 )w as fused onto the electron-rich heterabuckybowl trichalcogenasumanene( D 2 )t hrougha ne lectron-deficient pyrazine unit (A) to give 1c, 1d, 2c,a nd 2d,f eaturing the D 1 -A-D 2 structure. Both D 1 and D 2 play ap ivotalr ole in intramolecular charge-transfer (ICT) transitions, consequently 1c, 2d, 2c, and 2d show ab road ICT band at 450-720 nm in steady state. They exhibit two charge-separated transient states, CS 1 and CS 2 ,t hat appear in sequence. CS 1 has as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 168 publications
0
3
0
1
Order By: Relevance
“…Applying their synthetic strategy toward the pyrazine-fused trichalcogenasumanenes 244.2 , Shao et al prepared a series of new D 1 –A–D 2 π-systems C22.1aa – bb consisting of the electron-donating tetrathiafulvalene (D 1 ) and trichalcogenasumanene (D 2 ) units connected through an electron-accepting pyrazine unit (A) ( Chart 22 ). 454 These compounds displayed a broad absorption band (λ = 450–720 nm) as a consequence of intramolecular charge transfer (ICT) transition contributed by both D 1 and D 2 . Femtosecond transient absorption (fs-TA) measurements were carried out under photoexcitation at λ = 385 nm.…”
Section: Nonbenzenoid Fusionmentioning
confidence: 99%
“…Applying their synthetic strategy toward the pyrazine-fused trichalcogenasumanenes 244.2 , Shao et al prepared a series of new D 1 –A–D 2 π-systems C22.1aa – bb consisting of the electron-donating tetrathiafulvalene (D 1 ) and trichalcogenasumanene (D 2 ) units connected through an electron-accepting pyrazine unit (A) ( Chart 22 ). 454 These compounds displayed a broad absorption band (λ = 450–720 nm) as a consequence of intramolecular charge transfer (ICT) transition contributed by both D 1 and D 2 . Femtosecond transient absorption (fs-TA) measurements were carried out under photoexcitation at λ = 385 nm.…”
Section: Nonbenzenoid Fusionmentioning
confidence: 99%
“…碗状共轭分子7具有良好的空穴 迁移率(μ h = 0.32 cm 2 V −1 s −1 ) [43] , 而勺状共轭分子42 则可用于制作光电晶体管(phototransistor)且表现出极 高的光响应性(photo sensitivity, 2.58×10 7 ) [44] . 基于化合 物20/40, 我们也成功地将四硫富瓦烯与杂化素馨烯通 图 12 磷元素和硫族元素共同杂化素馨烯的合成(网络版彩图) 图 13 基于硫族元素杂化素馨烯开环反应的荧光分子合成(网络版彩图) 邵向锋: 碗状共轭分子"杂化素馨烯"的设计合成及可控化学转化 过吡嗪单元融合, 形成了"给体-受体-给体"型勺状共轭 分子 [45] . 此类分子对单线态氧以及酸具有超高灵敏响 应, 而且在飞秒和皮秒时间尺度上具有不同的激发态 吸收.…”
Section: 合成具有强红色荧光的共轭稠杂环unclassified
“…The pyrazine-fused trichalcogenasumanenes have been assembled via the transformation of 1,2-dibutoxybenzene unit into the corresponding ortho -quinones by means of FeCl 3 in CH 2 Cl 2 /MeCN at room temperature ( Scheme 44 ) [ 79 81 ]. Interestingly, it was observed that 1,2-dibutoxy groups could be selectively transformed to the ortho -quinones in the presence of FeCl 3 .…”
Section: Reviewmentioning
confidence: 99%